2016
DOI: 10.1111/vsu.12436
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Ultrasound to Predict the Location of Solitary Hepatic Masses in Dogs

Abstract: Ultrasound was specific but not sensitive for localizing hepatic masses, and localization accuracy was influenced by mass location and the presence of concurrent liver pathology. These findings should be taken into consideration by veterinary surgeons using ultrasound examination to guide patient treatment and surgical planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 31 publications
2
23
0
1
Order By: Relevance
“…Thereby, left-sided masses could be over-represented in the present study. Nevertheless, our reported mass distribution approximates those in previous studies and on necropsy (Patnaik et al 1980, Wormser et al 2016.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Thereby, left-sided masses could be over-represented in the present study. Nevertheless, our reported mass distribution approximates those in previous studies and on necropsy (Patnaik et al 1980, Wormser et al 2016.…”
Section: Discussionsupporting
confidence: 88%
“…In contrast, ultrasound remains heavily utilised for preoperative planning in veterinary medicine. A prior report has demonstrated that ultrasound has relatively high specificity and poor sensitivity for localising hepatic masses, and that mass location influences accuracy of localisation (Wormser et al 2016). Also, it was shown that masses arising from the left or right division were more likely to be correctly localised than those arising from the central division.…”
Section: Introductionmentioning
confidence: 99%
“…The right and central divisional lobes are typically fused to some degree near the hilus . The right lateral and right medial liver lobes are adhered to portions of the caudal vena cava, which increases the risk of intraoperative hemorrhage during resection . The central divisional lobes (right medial and quadrate) often must be removed en bloc because of the fact that they share closely associated vasculature, and failure to do so may result in necrosis of the remaining lobe .…”
Section: Discussionmentioning
confidence: 99%
“…The right lateral and right medial liver lobes are adhered to portions of the caudal vena cava, which increases the risk of intraoperative hemorrhage during resection . The central divisional lobes (right medial and quadrate) often must be removed en bloc because of the fact that they share closely associated vasculature, and failure to do so may result in necrosis of the remaining lobe . By comparison, the left divisional lobes are largely separate from each other and more mobile than the other liver lobes, with less parenchyma adjacent to the hilus, making left divisional lobectomies more surgically feasible .…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative assessment of hepatic mass lesions usually involves ultrasonography or CT, although there are few reports of the results of these studies in dogs. In a recent study of 137 dogs, ultrasonography correctly determined the site (division) of a hepatic mass in only 52% cases (Wormser et al 2016). CT enabled localisation of a hepatic mass in the right lateral lobe and facilitated complete surgical resection in a dog with hepatocellular carcinoma (Kneissl et al 1997a).…”
Section: Introductionmentioning
confidence: 99%